“Vote MDB. Você sabe por quê.”: estudo do discurso democrático emedebista na primeira fase da transição política (1974-1979) - estudo do discurso democrático medebista na primeira fase da transição política (1974-1979) - Queiroz, Pedro Henrique Gomes de (2021)
This research presents a study on the discourse collectively constructed by the Brazilian Democratic Movement (MDB), party which fulfilled the function of being the institutional opposition to the governments of the bourgeois-military dictatorship from 1966 to 1979. The core theme of analysis was the concept of democracy built by this party during the first phase of the political transition, the “detente” (1974-1979), a period which saw a tactical reorientation of the regime and an electoral rise of the MDB. To understand this concept, documents produced at the national level by the institute of political studies of the party were analysed, in light of the discourse analysis theorized by Mikhail Bakhtin. On this theoretical-methodological ground, it was possible to recover the contradictory process of production of this discourse, the internal correlation of forces, as well as the connexions established between the party and the different factions of the opposition and the State heading bourgeois-military bloc itself. A conclusion was reached that the labour and liberal heritages of the party based much of its political strategy, grounded on building a multiclass front, with bourgeois leadership, for the liberal democratization of the country and the erection of a welfare state. Such concept influenced much of the opposition, since this party took upon itself the mantle of the inescapable party if one aimed at overcoming the regime, through and ample and contradictory conciliation of interest by the working class and the associated-dependent bourgeoisie